Status epilepticus related rhabdomyolysis and acute kidney injury - Kula, Atay Can; Ulucan, Eda; Hoca, Emre; Ataoğlu, Hayriye Esra (International Journal Of Community Medicine And Public Health, 2019)
Rhabdomyolysis is a syndrome characterized by muscle necrosis and the release of intracellular muscle constituents into the circulation. Creatine kinase levels are typically markedly elevated, and muscle pain and myoglobinuria may be present. Its causes are variable. Acute kidney injury is a common complication of rhabdomyolysis. Our patient is a 51-year-old male who was brought to the hospital with a complaint of generalized tonic-clonic seizures and weakness. His creatine phosphokinase levels increased on the first day of admission to 93,809 U/l. Creatinine level was found to be 9.13 mg/dl in the first biochemistry test. He was diagnosed to have an acute kidney injury and rhabdomyolysis. Hemodialysis was not performed to patient. Sixteen days after first admission, the patient’s rhabdomyolysis resolved.